Psychometric Properties of the English and Malay Version of the Adapted Schutte Emotional Intelligence Scale - Ahmad, Nor Aniza; Praveena, Sarva Mangala; Tee, Ker Shin (Frontiers in Psychology, 2022)
ABSTRACT The study examines the psychometric properties of adapted Schutte Emotional Intelligence Scale (A-SEIS) with 200 undergraduate students at University Putra Malaysia (UPM). Upon the permission, the researchers adapted the original instrument, SEIS by incorporating a new construct which is understand emotions and some ability-based items into the perceive emotions construct. The A-SEIS is a mixed (trait and ability) measure EI instrument aims at assessing four important dimensions of EI, including perceive of emotions, utilize of emotions, understand of emotions, and manage of emotions. The study investigated the content validity of the A-SEIS by using the content validity indexing (CVI). Three expert panels translated and back translated the A-SEIS and rated for the degree of relevant of every item based on the four point scale provided in content validation form. The Exploratory Factor Analysis (EFA) methods were used to explore the underlying structure of A-SEIS. The general validity testing of the adapted instrument was carried out in the framework of the structural equation modeling (SEM) approach by applying two iterations of CFA, first approach is the Covariance based Structural Equation Modeling (CB-SEM) approach, followed by Partial Least Squares based Structural Equation Modeling (PLS-SEM) using two different software: AMOS and smartPLS. Research findings concluded the instrument is reliable and valid to be applied in tertiary education settings and future research.